Oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst as well as preparation method and application thereof

By developing an oxygen vacancies Bi2O2CO3/MIL-101-NH2 composite catalyst and using photocatalytic activation of persulfate, the problems of limited application of antibiotic water treatment and long degradation time in the prior art were solved, and efficient and economical antibiotic removal effect was achieved.

CN119633904AActive Publication Date: 2025-03-18GUIZHOU UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411661593.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing photocatalytic and persulfate oxidation technologies are limited in the treatment of antibiotic water, have a long degradation time, and are complex in the preparation method.

Method used

An oxygen vacancies Bi2O2CO3/MIL-101-NH2 composite catalyst was developed, and a composite material with a heterojunction structure was formed by solanothermal method and hydrothermal method was synthesized to form a composite material with a heterojunction structure, and photocatalytic activation of persulfate (PMS) was used to degrade antibiotics.

Benefits of technology

The composite catalyst efficiently removes antibiotics from water in a short period of time, with a degradation rate of 100%, which is significantly better than monomer materials, and has good cost-effectiveness and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633904A_ABST
    Figure CN119633904A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalytic oxidation and the field of water environment treatment. According to the composite catalyst provided by the invention, MIL-101-NH2 is loaded on the surface of Bi2O2CO3, so that a heterojunction structure rich in oxygen vacancies is formed; the Bi2O2CO3 is of a cluster flower-shaped structure with the diameter of 2 to 3 [mu] m; the MIL-101-NH2 is of a fusiform particle structure with the length of 500-1000 nm, is rich in oxygen vacancies, and is dispersed and loaded in the stamens of the Bi2O2CO3. The composite catalyst provided by the invention shows relatively high catalytic oxidation performance in a test of treating an antibiotic water body by photocatalytic activation of peroxymonosulfate (PMS), can effectively remove antibiotics in water within a short time, and has excellent application potential in antibiotic treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, the field of persulfate catalytic oxidation and the field of water environment management, and in particular to an oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst and a preparation method and application thereof. Background Art

[0002] Antibiotics are widely used in human medicine, animal husbandry and aquaculture. However, humans or livestock cannot fully absorb or metabolize antibiotics, so a large part of the ingested antibiotics will be discharged into the environment, causing the accumulation of antibiotics in the environment. The environmental release and pollution of antibiotics may promote the development and spread of antibiotic resistance, undermine the effectiveness of human drug effects, and seriously threaten human health and environmental safety. Therefore, it is necessary to further deepen the research on antibiotic treatment technology and develop economical and efficient antibiotic treatment methods to degrade difficult-to-remove antibiotic molecules into low-toxic small molecules.

[0003] Advanced oxidation technology can produce a variety of reactive oxygen species (ROS) for the degradation of antibiotics, degrading antibiotics into low-toxic small molecule intermediates, and has great application potential in the treatment of antibiotic wastewater. Among them, photocatalysis and persulfate oxidation technology have attracted much attention. Photocatalysis uses green and clean solar energy to stimulate photogenerated charges, and then produces ROS to degrade pollutants in water. Advanced oxidation technology based on persulfate activation can produce sulfate radicals (SO4 -· , E0=2.5-3.1V), has strong adaptability and high reaction efficiency, and has attracted widespread attention from scholars at home and abroad.

[0004] Photocatalysis has been extensively studied in the past few decades and has shown significant advantages in water treatment as a heterogeneous catalytic process. However, compared with traditional advanced oxidation technologies, the application of photocatalysis in actual water treatment systems is very limited. The synergistic effect of photocatalysis and persulfate oxidation can promote the removal of antibiotics, and the photogenerated electrons can be captured by persulfate and participate in the formation of sulfate radicals. At the same time, the consumption of photogenerated charges can inhibit the recombination of photogenerated charges and improve the photocatalytic activity. For example, Tong et al. synthesized boron-doped C3N5 for the degradation of 5 mg / L tetracycline in a heterogeneous photocatalytic combined peroxymonosulfate system, and photocatalytically activated persulfate within 120 minutes, achieving efficient degradation of tetracycline (Wu.et al, Peroxymonosulfate activation by boron doped C3N5 metal-freematerials with n→π*electronic transitions for tetracycline degradation undervisible light: Insights into the generation of reactive species, Doi.org / 10.1016 / j.cej.2023.147693). However, its preparation method is complicated and the reaction time is long.

[0005] CN117380285A provides a photocatalytic membrane system based on Bi2O2CO3-UIO-66-NH2 heterojunction catalyst, which can achieve a 100% degradation rate of tetracycline within 50 minutes under the synergistic effect of photocatalysis and membrane filtration. However, this method still relies on photocatalytic degradation of pollutants, and the degradation time is relatively long. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention provides an oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst and its preparation method and application. The composite catalyst provided by the present invention exhibits high catalytic oxidation performance in the test of photocatalytic activation of peroxymonosulfate (PMS) to treat antibiotic water, and can effectively remove antibiotics in water in a short time, and has excellent application potential for antibiotic treatment.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] An oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst, wherein the composite catalyst is a composite material having a heterojunction structure in which MIL-101-NH2 is loaded on the surface of Bi2O2CO3;

[0009] The Bi2O2CO3 is a clustered flower-like structure with a diameter of 2-3 μm; the MIL-101-NH2 is a spindle-like particle structure with an average particle size of 500-1000 nm, rich in oxygen vacancies, and tightly fits in the center of the flower-like Bi2O2CO3, forming a new Fe-Bi heterojunction.

[0010] Preferably, the MIL-101-NH2 is synthesized by a solvothermal method, wherein FeCl3·6H2O and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide (DMF), mixed evenly, and then subjected to a solvothermal reaction to generate MIL-101-NH2;

[0011] 12-24 mL of DMF is required as solvent for each addition of 1-2 mmol of FeCl3·6H2O, and the molar ratio of FeCl3·6H2O to 2-aminoterephthalic acid is 8-9:1-2.

[0012] Preferably, the solvent thermal reaction temperature is 100-120° C., and the reaction time is 22-26 hours.

[0013] Preferably, the Bi2O2CO3 / MIL-101-NH2 composite catalyst is synthesized by a hydrothermal method, wherein MIL-101-NH2, Bi(NO3)3·5H2O and C6H5Na3O7 are dissolved in deionized water, mixed evenly and then subjected to a hydrothermal reaction to generate Bi2O2CO3 / MIL-101-NH2;

[0014] According to the mass ratio, Bi(NO3)3·5H2O:C6H5Na3O7:MIL-101-NH2=14-18:10-16:1-3;

[0015] The amount of deionized water used is 34-69 mL of deionized water as a solvent for every 1-2 g of Bi(NO3)3·5H2O added.

[0016] Preferably, the pH is adjusted to 9-10 with aqueous ammonia before the hydrothermal reaction, the hydrothermal reaction temperature is 160-200° C., and the reaction time is 22-25 hours.

[0017] The present invention also provides an application of the oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst, wherein the composite catalyst is used as a photocatalyst to activate persulfate to degrade antibiotics in water under visible light irradiation.

[0018] Furthermore, the specific method for degrading antibiotics is: adding Bi2O2CO3 / MIL-101-NH2 composite catalyst as a photocatalyst to water containing antibiotics, adding persulfate after the photocatalyst reaches adsorption-desorption equilibrium under dark conditions, and generating oxidative active substances to degrade antibiotics under visible light irradiation.

[0019] Preferably, the wavelength of the visible light is greater than 400 nm, and the persulfate is peroxymonosulfate.

[0020] Preferably, the antibiotic is tetracycline; and the pH range of the water containing the antibiotic is 5-9.

[0021] Preferably, the added concentration of the Bi2O2CO3 / MIL-101-NH2 composite catalyst is 0.1-0.3 g / L, and the added concentration of the persulfate is 0.7-1.1 mM.

[0022] Furthermore, the concentration of the antibiotic in the water body is in the range of 0-100 mg / L, preferably 0.01-100 mg / L.

[0023] The beneficial technical effects of the present invention are:

[0024] 1. The present invention is different from the traditional MIL-101-NH2 preparation method in which the molar ratio of FeCl3·6H2O:2-aminoterephthalic acid is set to 2:1. Instead, the addition ratio of FeCl3·6H2O to 2-aminoterephthalic acid is greatly increased to 8:1, thereby obtaining MIL-101-NH2 with more MOF metal cluster active sites and improving the photocatalytic activity.

[0025] 2. The present invention combines MIL-101-NH2 with Bi2O2CO3. The MIL-101-NH2 particles occupy the growth sites of Bi2O2CO3, so that the originally randomly distributed nanosheets are stacked to form thick petals, forming a "bud blooming" morphology effect. From the perspective of photoelectric properties, the surface is loaded with transition metal MOFs with excellent photoelectric properties, which effectively inhibits the separation of photogenerated electrons and holes, and constructs a new Fe-Bi heterojunction catalyst with excellent photocatalytic activity.

[0026] 3. The heterojunction material prepared by the present invention contains oxygen vacancies and transition metals, which can promote charge transfer and iron ion valence state conversion on the surface of the catalytic material, enhance the activation ability of persulfate, and can continuously generate 1 O2 and SO4 -· To improve the degradation ability, it is beneficial to improve the removal effect of antibiotics.

[0027] 4. The Bi2O2CO3 / MIL-101-NH2 heterojunction material provided by the present invention can activate persulfate to produce a large amount of ROS through two pathways: photogenerated charges generated by photocatalysis and transition metal ions of MOF, thereby efficiently degrading antibiotics.

[0028] 5. The Bi2O2CO3 / MIL-101-NH2 heterojunction material provided by the present invention shows good cost-effectiveness and application prospects for treating tetracycline in wastewater. Compared with the degradation rate of about 84% in CN117380285A in 20 minutes, the optimal degradation rate of the present invention in 20 minutes can reach 100%, which is of great significance for the development of efficient and economic antibiotic wastewater treatment. The present invention adopts a photocatalytic coupling persulfate system, which greatly enhances the application potential in actual water treatment systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 SEM images of the flower-shaped Bi2O2CO3 (a), spindle MIL-101-NH2 (b) and composite material Bi2O2CO3 / MIL-101-NH2 (cd) in Example 2;

[0030] Figure 2 X-ray diffraction (XRD) patterns of Bi2O2CO3, MIL-101-NH2 and the composite material Bi2O2CO3 / MIL-101-NH2 in Example 2;

[0031] Figure 3 is the electron spin resonance (ESR) spectra of Bi2O2CO3, MIL-101-NH2 and the composite material Bi2O2CO3 / MIL-101-NH2 in Example 2;

[0032] Figure 4 This is a comparison chart of the degradation performance of Bi2O2CO3, MIL-101-NH2 and Bi2O2CO3 / MIL-101-NH2 composite material in Test Example 1 for 10 mg / L tetracycline under visible light and 0.9 mM PMS conditions;

[0033] Figure 5 This is a comparison chart of the degradation performance of the material Bi2O2CO3 / MIL-101-NH2 obtained in Test Example 2 for degrading tetracycline of different concentrations under visible light and 0.9 mM PMS conditions;

[0034] Figure 6 This is a comparison chart of the degradation performance of the material Bi2O2CO3 / MIL-101-NH2 obtained in Test Example 3 to tetracycline solutions of different pH values ​​under visible light and 0.9 mM PMS conditions;

[0035] Figure 7This is a graph showing the reuse performance of the material Bi2O2CO3 / MIL-101-NH2 obtained in Test Example 4 in degrading tetracycline under visible light and 0.9 mM PMS conditions. DETAILED DESCRIPTION

[0036] The exemplary implementation cases of the present disclosure are now described in detail. Although exemplary embodiments of the present disclosure are shown, it should be clear that the figures and embodiments shown in the exemplary embodiments of the present disclosure are only part of the invention and should not be considered as limitations of the present invention. These embodiments are provided to enable researchers in the field to have a clearer understanding of the present disclosure.

[0037] Embodiment 1:

[0038] 5 mmol of FeCl3·6H2O and 0.625 mmol of 2-aminoterephthalic acid were dissolved in 60 ml of DMF. After magnetic stirring for 0.5 h, the mixed solution was placed in a reactor for constant temperature reaction at 110°C for 24 h. After the reaction, it was centrifuged, washed, and dried at 60°C for 8 h to obtain MIL-101-NH2.

[0039] 50 mg of pre-prepared MIL-101-NH2, 1.5 mmol of Bi(NO3)3·5H2O (0.73 g) and 2.25 mmol of C6H5Na3O7 (0.58 g) were dissolved in 25 mL of deionized water, stirred evenly and the mixed solution was adjusted to pH = 9 with ammonia water. After magnetic stirring, the mixed solution was transferred to a reactor and reacted at 180°C for 24 hours. The reacted material was washed with ethanol and deionized water several times, and the sample obtained after drying at 60°C overnight was recorded as Bi2O2CO3 / MIL-101-NH2-50 composite catalyst.

[0040] Embodiment 2:

[0041] The same as Example 1, the only difference is that the dosage of MIL-101-NH2 is 100 mg, and the final sample is recorded as Bi2O2CO3 / MIL-101-NH2-100 composite catalyst.

[0042] The SEM images of the materials prepared by the above method are as follows: Figure 1 As shown. Figure 1In (a), we can see that the surface of Bi2O2CO3 has many fine and curled nanosheet "petals" forming a clustered bud structure; in (b), we can see that MIL-101-NH2 shows a typical spindle structure with an average particle size of 500-1000nm, and most of the crystals are similar in size and have sharp edges; in (c), we can see that the surface morphology of the composite material has changed compared to Bi2O2CO3. The fine buds of Bi2O2CO3 gradually disperse, and the nanosheets gather to form thick petals with an average diameter of 2-3μm. The MIL-101-NH2 particles are embedded in the stamens, forming a new type of Fe-Bi heterojunction; in (d), we can see that the edges of the MIL-101-NH2 crystals gradually passivate to form smooth particles, which are embedded in the stamens of Bi2O2CO3.

[0043] The XRD pattern of the material prepared by the above method is shown in the attached Figure 2 As shown in the figure, it can be seen that MIL-101-NH2 shows a clear diffraction peak at 9.4°, while the characteristic peaks of Bi2O2CO3 are all indexed by tetragonal Bi2O2CO3 (JCPDS 84-1752). Bi2O2CO3 / MIL-101-NH2-100 retains the characteristic diffraction peaks of MIL-101-NH2 and Bi2O2CO3, and the diffraction intensities of the (013) and (110) crystal planes corresponding to 30.3° and 32.7° are reduced to a certain extent, which may be attributed to the stacking of nanosheets into thick petals and the lattice deformation caused by the inlay of MIL-101-NH2.

[0044] The ESR spectrum of the prepared material is shown in Figure 3 As shown, it can be seen that different signal peaks at g = 2.013 are observed in the prepared photocatalysts, indicating the presence of oxygen vacancies. However, the oxygen vacancy signal of Bi2O2CO3 / MIL-101-NH2-100 is weaker than that of MIL-101-NH2, which may be attributed to the collapse of some oxygen vacancies during the synthesis process.

[0045] Embodiment 3:

[0046] The same as Example 1, the only difference is that the dosage of MIL-101-NH2 is 150 mg, and the final sample is recorded as Bi2O2CO3 / MIL-101-NH2-150 composite catalyst.

[0047] Test Example 1: Comparison of tetracycline degradation between composite catalyst and monomer material in PMS system

[0048] Accurately weigh 20 mg of Bi2O2CO3 / MIL-101-NH2-100 composite photocatalytic material, a single cluster flower-shaped Bi2O2CO3 with a diameter of 2-3 μm, and a spindle-shaped MIL-101-NH2 material with a particle size of 500-1000 nm, and add them into 100 mL of a 10 mg / L tetracycline solution respectively. After 30 minutes of dark reaction to reach adsorption and desorption equilibrium, turn on the xenon lamp and add 0.9 mM PMS at the same time. Sampling is performed at certain time intervals (0, 2, 5, 10, 20 min), and the remaining tetracycline concentration is determined on a high performance liquid chromatograph to evaluate the degradation efficiency of each catalyst on tetracycline.

[0049] The results of the degradation effects of various catalysts on tetracycline are as follows Figure 4 As shown by Figure 4 It can be seen that after 20 minutes of reaction under visible light irradiation and 0.9Mm PMS conditions, the removal rates of single materials Bi2O2CO3 and MIL-101-NH2 were 77.8% and 89.2% respectively. Under the same conditions, the degradation efficiency of the composite material Bi2O2CO3 / MIL-101-NH2 was significantly improved, and the degradation rate was increased to 100%, which was significantly better than the monomer material. The photocatalytic activity of the monomer material is relatively low, and the construction of the heterojunction effectively inhibits the recombination of photogenerated carriers, improves the photocatalytic activity, and promotes the migration of photogenerated carriers. Compared with the simple photocatalytic system, the photocatalytic activation PMS system adopted in the present invention not only activates PMS through the photogenerated electrons generated by photocatalysis in addition to the traditional photocatalytic pathway to degrade pollutants, but also the Fe transition metal in the heterojunction material can activate PMS to produce a large amount of ROS, which has a more efficient and rapid degradation effect on tetracycline.

[0050] Test Example 2: Comparison of the degradation effects of composite catalysts on tetracycline at different concentrations

[0051] 20 mg Bi2O2CO3 / MIL-101-NH2-100 composite material was accurately weighed and added to 100 mL tetracycline solution with initial concentrations of 5, 10, and 20 mg / L. After 30 minutes of dark reaction to reach adsorption-desorption equilibrium, the xenon lamp was turned on and 0.9 mM PMS was added at the same time. Samples were taken at certain time intervals (0, 2, 5, 10, 20 min) and the residual tetracycline concentration was measured on a high performance liquid chromatograph to evaluate the degradation efficiency of each catalyst for tetracycline.

[0052] The results of the degradation effects of heterojunction catalysts on tetracycline at different concentrations are shown in Figure 2. Figure 5 As shown by Figure 5It can be seen that when the tetracycline concentration increases from 5 mg / L to 20 mg / L, the degradation efficiency of Bi2O2CO3 / MIL-101-NH2 decreases from 100% to 82.6%. This is because as the concentration of tetracycline increases, more tetracycline molecules will consume the free radicals and holes of the catalyst, thereby reducing the removal efficiency of tetracycline.

[0053] Test Example 3: Comparison of the degradation effects of different reaction pH on tetracycline

[0054] 20 mg of Bi2O2CO3 / MIL-101-NH2-100 composite material was accurately weighed and added to 100 mL of 10 mg / L tetracycline solution with different solution pH (3, 5, 7, 9, 11). After 30 minutes of dark reaction to reach adsorption and desorption equilibrium, the xenon lamp was turned on and 0.9 mM PMS was added at the same time. Samples were taken at certain time intervals (0, 2, 5, 10, 20 min) and the remaining tetracycline concentration was determined on a high performance liquid chromatograph to evaluate the degradation efficiency of each catalyst for tetracycline.

[0055] The degradation effect of different reaction pH on tetracycline Figure 6 As shown by Figure 6 It can be seen that the optimal degradation pH of Bi2O2CO3 / MIL-101-NH2 is between 5 and 9. When the degradation solution is acidic, especially when pH=3, the degradation rate drops to 70.8%. This is because the free radicals O2 excited by the photocatalyst under acidic conditions - Easy to be H + consumption, resulting in a decrease in the concentration of active oxygen species and a decrease in the photocatalytic degradation efficiency.

[0056] Test Case 4: Reusability

[0057] Accurately weigh 20 mg Bi2O2CO3 / MIL-101-NH2-100 composite material and add it to 100 mL tetracycline solution with a concentration of 10 mg / L. After dark reaction for 30 minutes to reach adsorption and desorption equilibrium, turn on the xenon lamp and add 0.9 mM PMS to start the degradation reaction. The dark reaction plus light reaction treatment for 50 minutes is a cycle. After one cycle, the reaction solution is centrifuged and dried to collect the catalyst, and the next cycle is carried out. The remaining tetracycline concentration is measured on a high-performance liquid chromatograph to evaluate the degradation efficiency of each catalyst for tetracycline. It should be noted that each cycle includes the 30 minutes required for adsorption equilibrium.

[0058] Reuse performance results such as Figure 7 As shown, the horizontal axis is the degradation time (Time), and the vertical axis is the degradation rate of tetracycline (C t / C0), where C0 is the initial concentration of tetracycline, C tis the real-time concentration. After four degradation cycles, the Bi2O2CO3 / MIL-101-NH2-permonosulfate system can still maintain 84.5% tetracycline degradation efficiency, showing excellent reuse performance.

[0059] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. An oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst, characterized in that: The composite catalyst is a composite material with a heterojunction structure in which MIL-101-NH2 is loaded on the surface of Bi2O2CO3; The Bi2O2CO3 is a clustered flower-like structure with a diameter of 2-3 μm; the MIL-101-NH2 is a spindle-like particle structure with an average particle size of 500-1000 nm, rich in oxygen vacancies, and tightly fits in the center of the flower-like Bi2O2CO3, forming a new Fe-Bi heterojunction.

2. The composite catalyst according to claim 1, characterized in that The MIL-101-NH2 is synthesized by a solvothermal method, wherein FeCl3·6H2O and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide (DMF), mixed evenly, and then subjected to a solvothermal reaction to generate MIL-101-NH2; 12-24 mL of DMF is required as solvent for each addition of 1-2 mmol of FeCl3·6H2O, and the molar ratio of FeCl3·6H2O to 2-aminoterephthalic acid is 8-9:1-2.

3. The composite catalyst according to claim 2, characterized in that The solvent thermal reaction temperature is 100-120° C., and the reaction time is 22-26 hours.

4. The composite catalyst according to claim 1, characterized in that The Bi2O2CO3 / MIL-101-NH2 composite catalyst is synthesized by a hydrothermal method, wherein MIL-101-NH2, Bi(NO3)3·5H2O and C6H5Na3O7 are dissolved in deionized water, mixed evenly and then subjected to a hydrothermal reaction to generate Bi2O2CO3 / MIL-101-NH2; According to the mass ratio, Bi(NO3)3·5H2O:C6H5Na3O7:MIL-101-NH2=14-18:10-16:1-3; The amount of deionized water used is 34-69 mL of deionized water as a solvent for every 1-2 g of Bi(NO3)3·5H2O added.

5. The composite catalyst according to claim 4, characterized in that Before the hydrothermal reaction, the pH is adjusted to 9-10 with ammonia water, the hydrothermal reaction temperature is 160-200° C., and the reaction time is 22-25 hours.

6. Use of the oxygen vacancy type Bi2O2CO3 / MIL-101-NH2 composite catalyst according to any one of claims 1 to 5, characterized in that: The composite catalyst is used as a photocatalyst to activate persulfate to degrade antibiotics in water under visible light irradiation.

7. The use according to claim 6, characterized in that: The specific method for degrading antibiotics is: adding Bi2O2CO3 / MIL-101-NH2 composite catalyst as a photocatalyst to water containing antibiotics, adding persulfate after the photocatalyst reaches adsorption-desorption equilibrium under dark conditions, and generating oxidative active substances to degrade antibiotics under visible light irradiation.

8. The use according to claim 7, characterized in that: The wavelength of the visible light is greater than 400 nm, and the persulfate is peroxymonosulfate.

9. The use according to claim 7, characterized in that: The antibiotic is tetracycline; the pH range of the water containing the antibiotic is 5-9.

10. The use according to claim 7, characterized in that: The added concentration of the Bi2O2CO3 / MIL-101-NH2 composite catalyst is 0.1-0.3 g / L, and the added concentration of the persulfate is 0.7-1.1 mM.

Citation Information

Patent Citations

  • Fe(III) / Bi2O2CO3 photocatalyst preparation method

    CN105749945A

  • Preparation method of iron sesquioxide-bismuthylcarbonate composite light catalyst

    CN106268895A

  • Preparation method of Fe-doped Bi2O2CO3 photocatalyst and Fe-doped Bi2O2CO3 photocatalyst

    CN108212187A

  • Bismuth-rich bismuth oxybromide / metal organic framework composite photocatalyst as well as preparation method and application thereof

    CN115532320A

  • Z-type heterojunction Bi2O2CO3 / UIO-66-NH2 composite material as well as preparation method and application thereof

    CN117380285A